Systém odměňování zaměstnanců a návrhy na jeho zlepšení ve vybrané společnosti - Doležalová, Daniela (Vysoké učení technické v Brně. Fakulta podnikatelská, 2023)
Bakalářská práce se zabývá analýzou zavedeného systému odměňování ve vybrané společnosti XYZ s. r. o. a dodává návrhy na zlepšení. Bakalářská práce má tři části. První část je teoretická, kde je vysvětlena problematika s pomocí odborné literatury. Druhá část je analytická, která vysvětluje systém odměňování v daném podniku. Poslední je část návrhová, v níž jsou přiblíženy návrhy na zlepšení systému odměňování. Vychází se zde z analytické části.

The bachelor thesis deals with the analysis of the established remuneration system in the selected company XYZ s. r. o. and provides suggestions for improvement. The bachelor thesis has three parts. The first part is theoretical where the issue is explained with the help of literature. The second part is analytical which explains the remuneration system in the company. The last part is the suggestion part, here suggestions for improving the reward system are approached. This is based on the analytical part.
Employee remuneration system and suggestions for its improvement in the selected company
Keywords: zaměstnanci; společnost; odměňování; mzda; benefity zaměstnanců; employees; company; remuneration; salary; employee benefits